CityZoom UP (Urban Pollution): a computational tool for the fast generation and setup of urban scenarios for CFD and dispersion modelling simulation - Grazziotin, Pablo Colossi (2016)
This research presents the development of CityZoom UP, the first attempt to extend existing urban planning software in order to assist in modelling urban scenarios and setting up simulation parameters for Gaussian dispersion and CFD models. Based on the previous capabilities and graphic user interfaces of CityZoom to model and validate urban scenarios based on Master Plan regulations, new graphic user interfaces, automatic mesh generation and data conversion algorithms have been created to seamlessly generate input data for dispersion model AERMOD and CFD packages CFX and OpenFOAM.